2008
DOI: 10.3855/jidc.229
|View full text |Cite
|
Sign up to set email alerts
|

A case report and review of the literature: Ciprofloxacin resistant Salmonella enterica serovar Typhi in India

Abstract: Background: Enteric fever is a major public health problem in India. The current treatment of choice is the fluoroquinolones. Methods: The minimum inhibitory concentration (MIC) of ciprofloxacin was determined by E-test, HIMEDIA HiComb MIC test and agar dilution. Results: An isolate of Salmonella enterica serovar Typhi (S. Typhi) from a case of enteric fever gave a ciprofloxacin MIC of 64µg/ml. Conclusions: To our knowledge there have been no reports of such high-level resistance to ciprofloxacin in S. Typhi f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
0
27
1
Order By: Relevance
“…A single mutation in quinolone-resistance-determining region of gyr A gene is sufficient to confer resistance to NA and reduced susceptibility to fluoroquinolones. The continued use of ciprofloxacin against NA R strains has led to a steady creep in ciprofloxacin MICs [7,16,19] along with further mutations at the same locus, resulting in recent emergence of fully resistant strains [7,8,[20][21][22]. Saha et al, in 2006, reported a highly ciprofloxacin-resistant S. Typhi strain with the MIC as high as 512 μg/mL from Bangladesh [23].…”
Section: Discussionmentioning
confidence: 99%
“…A single mutation in quinolone-resistance-determining region of gyr A gene is sufficient to confer resistance to NA and reduced susceptibility to fluoroquinolones. The continued use of ciprofloxacin against NA R strains has led to a steady creep in ciprofloxacin MICs [7,16,19] along with further mutations at the same locus, resulting in recent emergence of fully resistant strains [7,8,[20][21][22]. Saha et al, in 2006, reported a highly ciprofloxacin-resistant S. Typhi strain with the MIC as high as 512 μg/mL from Bangladesh [23].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an increase in Salmonella serovar Paratyphi A isolates with ciprofloxacin MICs of Ն2 g/ml was reported from New Delhi in 2000 (347), and a ciprofloxacin-resistant isolate with a MIC of 128 g/ml was isolated in Japan in 2002 (348). By 2008, there were reports of ciprofloxacin-resistant Salmonella serovar Typhi from multiple centers in India (349)(350)(351)(352). In 2010, a tertiary hospital in Chandigarh, India, reported that 13.6% of isolates were ciprofloxacin resistant (353).…”
Section: Development Of Antimicrobial Resistance Among Typhoidal Salmmentioning
confidence: 99%
“…In 2008, there were reports of high level ciprofloxacinresistant Salmonella enteric from many centres in India, 21,22 including our study, prevalence was found to be 14.32%. By in vitro antibiotic sensitivity testing, our data also confirm that resistance to antimicrobial agents (Nalidixic acid, ciprofloxacin, trimethoprim, and sulfamethoxazole) has continued to increase at an alarming pace.…”
Section: Discussionmentioning
confidence: 83%